Is Positive accounting theory still relevan? - Zhafir, Muhammad Nafhan; Subroto, Bambang (PT. EQUATOR SINAR AKADEMIA, 2024)
This research studies the development, research and criticism of Positive Accounting Theory (TAP). This research uses a scoping review approach with five main steps to identify Positive Accounting Theory. total of 11 research articles were collected related to Positive Accounting Theory from 2012-2022 using internet search engines and library research. After going through the stages of literature selection and mapping, there were 3 articles which were explained further. This research uses literature study research, namely using secondary data. Data comes from previous research journals with discussions similar to the theme of this research. Positive accounting theory does not directly determine appropriate accounting policy choices for companies. In this case, choosing accounting policies will be easier if viewed from the management side. Because management has the desire to choose accounting policies for their company, this is also indicated for management to respond to changes that occur in the company environment, such as new accounting standards. Financial accounting standards were originally created by standards boards in each country, as a result, accounting standards between one country and another are very likely to differ. This causes several changes regarding the accounting methods that management can choose. This research concludes that Positive Accounting Theory is still relevant so that it can be used for current and future accounting research practices, although there are several criticisms of Positive Accounting Theory, in terms of methodology, philosophy and economic approach of Positive Accounting Theory. Therefore, future research will contribute to solving the TAP problem.